Student Experiences with Digital Learning Objects in Higher Education: A Qualitative Study - Pambudi; Ontu, Benediktus Kristianto Nobar (Generate Digital Publishing, 2026)
Objective: This study aims to explore university students' experiences and perceptions of using Digital Learning Objects (DLOs) in a distance-learning environment, particularly in supporting independent, interactive, and flexible learning. Research Design & Methods: This study employs a qualitative research design using in-depth interviews and focus group discussions with students at the Open University. Data were analyzed using thematic analysis to identify patterns related to usage, perceived benefits, challenges, and adaptive strategies in interacting with DLOs. Findings: The findings indicate that DLOs enhance learning flexibility, accessibility, independent learning, and digital literacy. However, students also face challenges such as technical issues, suboptimal pedagogical design, low motivation, and varying content quality. These challenges are addressed through adaptive strategies. The study also finds that learning experiences are influenced by individual characteristics and contextual factors. A conceptual model is developed, highlighting the interconnection between access, engagement, competence, motivation, and learning outcomes. Contributions: This study provides practical insights for educators, instructional designers, and policymakers in integrating DLOs into higher education. It emphasizes the importance of student-centered and contextually relevant approaches to improve engagement, autonomy, and learning outcomes. Novelty: This study offers a comprehensive conceptual model that captures the multidimensional interaction between technological, individual, and contextual factors in DLO-based distance learning, which has been limited in previous research.